Validation of landslide susceptibility using a GIS-based statistical model and Remote Sensing Data in the Amzaz watershed in northern Morocco - El-fengour, Abdelhak (2019)
The main objective of this research is to examine and validate the landslide susceptibility assessment (LSA)results of the spatial probability of landslide occurrence in the Amzaz watershed area in Northern Morocco,setting out to create a helpful agent for the decision-makers of land-use policies. In order to reach the maingoal of this study, two sub-objectives were defined: the presenting of the physiography and the cartographyof the geographical components of the study area, and the analysis of the LSA using a statistical-basedmethod, Information Value Method (IVM), as a criteria required by the Model. Lastly, the validation of theresults through the prediction and success rates was carried out. Landslide susceptibility is the probabilitythat landslides will be generated in the predicted zone depending on local terrain characteristics.Several methods are proposed for landslide susceptibility assessment worldwide. IVM has been applied toprepare the landslide susceptibility map. This paper envisages the definition of the settings of the study areaas well as the geophysical characteristics by means of the acquisition and preparation of predisposing factors,such as the geology, land use and climate and the application of the IVM on LSA using a statistically basedmethod for each subset of the landslide inventory.This study is aimed at a prediction vision for sustainability as an alternative and this is not limited todegradation processes. It also concerns the efforts made to adapt to the impacts and even those of mitigatingchange. The promotion of sustainable development in risk areas requires an effort to analyze and evaluatelocal practices and approaches. This is what we are trying to do through this work, which starts from amethodological basis to validate a model for predicting landslides affecting the Moroccan Central Rif area.